Printed matter / Drukwerk - Martens, Karel (London : Hyphen Press, 2010)
- Karel Martens : work in progress = werk in uitvoering / Robin Kinross##- 50 years of work = 50 jaar werk ; What design means for me = Wat vormgeving voor mij betekent / Karel Martens##- Martens' capture of the margin = Martens' verovering van de marge / Koosje Sierman##- Karel Martens : meticulous and personal = zorgvuldig en persoonlijk / Hugues C. Boekraad##- Karel Martens and education = Karel Martens over onderwijs##- Book keeping = Uit de boeken / Jaap van Triest.
Produced on the initiative of the Dr A.H. Heineken Foundation for Art.
Parallel text in English and Dutch.
boek
Keywords: Martens, Karel